Collision-induced absorption and electric quadrupole transitions of N2 by OF-CEAS near 4.0 µm and CRDS near 2.1 µm. (March 2019) - Richard, L.; Mondelain, D.; Kassi, S.; Ventrillard, I.; Romanini, D.; Campargue, A.
Highlights: The fundamental and first overtone bands of N2 are studied by CRDS and OFCEAS. High sensitivity measurements are performed near 2492 and 4720 cm −1 . The collision-induced absorption (CIA) is measured at sub-atmospheric pressure. The very weak 2–0 S(10) and S(11) are measured for the first time in the laboratory. Comparison to literature, in particular to the HITRAN database, is discussed. Abstract: Highly sensitive cavity enhanced laser techniques are used for accurate measurements of the absorption of dinitrogen (N2 ) at two spectral points of the fundamental and first overtone bands. Spectra of pure N2 and of a N2 /O2 mixture were recorded near 2491 and 4720 cm −1 by Optical Feedback Cavity Enhanced Absorption Spectroscopy (OF-CEAS) and Cavity Ring Down Spectroscopy (CRDS), respectively. The noise level of the OF-CEAS and CRDS spectra corresponds to a minimum detectable absorption, α min, of about 10 -9 and 10 - 11  cm −1, respectively. Measurements involve both the N2 collision-induced absorption (CIA) bands and the very weak 2–0 S (10) and S (11) electric quadrupolar transitions. Accurate CIA binary coefficients, B N 2 − N 2 and B N 2 − O 2, are derived from the pressure-squared dependence of the baseline level of the spectra recorded at pressures below 1 atm. These CIA values are compared to previous determinations from high pressure spectra (up to 90 atm) and to recent classical molecular dynamics simulations (CMDS). An overall good agreement is obtained although a significant deviation is observed for the first overtone CIA near 4720 cm −1 . The line position and intensity (on the order of a few 10 −30  cm/molecule) of the 2–0 S (10) and S (11) electric quadrupolar transitions are determined experimentally for the first time and compared to theoretical values provided in the HITRAN2016 database. Graphical abstract: Image, graphical abstract